Peran Psikologi Pendidikan dalam Pendidikan dan Pembelajaran Matematika di Sekolah - 'Alwan, Faiz Fatihul; Chaniago, Aulia Febliana (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Educational psychology as a branch of psychology has an essential role in education. History shows that educational psychology calls for education to develop over time, especially in mathematics education. The awareness about individual differences and the fact that students need psychological intervention, the more convincing the role of psychology in education in mathematics learning. This study describes the role of psychology in mathematics education. Using a qualitative approach with a literature study design, this research discusses the role of educational psychology in the learning process of mathematics, mathematics assessment, and mathematics education research.